Organochlorine Compounds in Beached Plastics and Marine Organisms - Nunes, Luís M. (Frontiers in Environmental Science, 2022)
Here we compare bioaccumulation factors (BAF) in marine organisms to partition ratios (PR) in marine debris for dichlorodiphenyltrichloroethane (DDTs) and polychlorinated biphenyls (PCBs). Both organochlorines (HOCs) are synthetic persistent organic pollutants emitted into the environment since the beginning of last century in approximately equal amounts. Their vast use and dispersion have resulted in approximately similar median concentrations of PCBs and DDTs in some pelagic organisms, namely in the liver and muscle tissue of fish. Molluscs, on the other hand, show higher median uptake of PCBs than of DDTs, probably reflecting more localized conditions. We found that the BAF can be several orders of magnitude higher than the PR. For instance, the median concentrations of HOCs in the different matrices of fish, birds and mammals are between one to four orders of magnitude higher than those found in marine debris, when lipid-normalized; or up to two orders of magnitude when measured as wet weight. But concentrations are similar for molluscs, which agrees with previous studies using passive samplers. Future research should focus on reducing sources of uncertainty by i) homogenization of chemical procedures; ii) better assessment of chemical partition equilibrium between water and polymers in environmental conditions; iii) use of (multi)polymer passive samplers better aimed at mimicking uptake of specific living tissues.